The adventures of Owen Hatherley in the post-Soviet space - Hatherley, Owen 1981- (Repeater Books, an imprint of Watkins Media Ltd., 2018)
"Nearly thirty years after the fall of the USSR, the word 'Soviet' should be as meaningless by now as 'Hapsburg' or 'Hohenzollern.' Strangely, though, it endures, as places both inside and outside the former Soviet Union define themselves for or against what happened when it existed. But does that experience mean anything today, or is it just an enormous cul-de-sac? This book tries to find out, through an itinerary that goes from the Baltic to Belarus, from Ukraine to the Urals, from the Caucasus to Central Asia, and in cities that range from nuclear new towns of the Fifties to gleaming new capitals of the 21st century. In this Eurasian post-Soviet space, we try to find the continuities with Communism - if there are any - and the remnants of revolutions both distant and recent. Instead of a wistful journey through ruins, this intends to be an engaged travelogue, a subjective, personal Marxist Humanist guidebook to somewhere that actually exists, but which is constantly haunted by what it didn't become, whether a real Communist utopia or a successful or fair capitalism. In the course of this transcontinental account of what used to be the Soviet Union and is now a patchwork of EU democracies, neoliberal dictatorships and Soviet nostalgic enclaves (often found in the same countries), we might just find the outlines of a way of building and living in cities that is a powerful alternative, both in the past and present."--From Amazon.com
Keywords: Postkommunismus; Stadt; Nachfolgestaaten; Sowjetunion; Former Soviet republics / Social conditions / 21st century; Russia (Federation) / History / 1991-; Asia, Central / History / 21st century; Russia (Federation) / Politics and government / 1991-; Politics and government; Social conditions; Central Asia; Russia (Federation); Soviet Union / Former Soviet republics; Since 1991; History; Reisebericht